Central line-associated bloodstream infections in the intensive care unit: importance of the care bundle - Atilla, Aynur (Korean J Anesthesiol, 2016)
BACKGROUND: The importance and efficacy of a care bundle for preventing central line-associated bloodstream infections (CLABSIs) and infectious complications related to placing a central venous catheter (CVC) in patients in the intensive care unit (ICU). METHODS: A care bundle was implemented from July 2013 to June 2014 in a medical ICU and surgical ICU. Data were divided into three periods: the prior period (July 2012–June 2013), the intervention period (July 2013–June 2014; first and second periods), and the post-intervention period (July 2014–December 2014; third period). A care bundle consisting of optimal hand hygiene, skin antisepsis with chlorhexidine (2%) allowing the skin to dry, maximal barrier precautions for inserting a catheter (sterile gloves, gown, mask, and drapes), choice of optimal insertion site, prompt catheter removal, and daily evaluation of the need for the CVC was introduced. RESULTS: The catheterization duration was longer and femoral access was more frequently observed in patients with CLABSIs. CLABSI rates decreased with use of the care bundle. The CLABSI rate in the medical ICU was 6.20/1,000 catheter days during the prior period, 3.88/1,000 catheter days during the intervention period, and 1.05/1,000 catheter days during the third period. The CLABSI rate in the surgical ICU was 8.27/1,000, 4.60/1,000, and 3.73/1,000 catheter days during these three periods, respectively. CONCLUSIONS: The choice of an optimal catheter insertion site, use of all barrier precautions, and removal of catheters when they are no longer needed are essential to decrease the CLABSI rate.